Impact of KVK in Transfering Knowledge to Tribal Farmers on Farm Activities (Global Journal of Science Frontier Research, 2015)
Krishi Vigyan Kendras (KVKs) are organising training programmes with the felt needs of the tribal farmers as per the resources available. The study conducted with 240 tribal farmers and farm women undertaken training at KVK in the districts of Sundergarh, Keonjhar and Nuapada revealed that there was overall increase of 36.82% of the knowledge level of the respondents on various farm activities. However, 33.00% gaps indicated that the tribal farmers and farm women were still lacking adequate knowledge. More gaps were observed on farm forestry, fish farming, income generating activities, farm mechanisation, animal production and horticulture in comparison to crop production. Socio-economic attributes of the respondents had not much influence in increasing their knowledge level. Hence, KVKs have to organise more need based training programmes to enrich knowledge and skill competency of the tribal farmers to adopt the changed practices for more production and income for their sustainable livelihood.
Keywords: Training; KVK; tribal; knowledge